Phenomenon-Based Learning in Teaching a Foreign Language: Experiences of Lithuanian Teachers - Nijole Ciuciulkiene; Ilona Tandzegolskiene-Bielaglove; Martyna Culadiene (Social Sciences, 2023)
Phenomenon-based learning (hereinafter PhenoBL) is widely studied in the majority of European countries, especially given that research data indicate that PhenoBL is more successful in providing effective learning, better student achievement, a stronger interest in science, and even a higher happiness index. However, there are sparse data on the educational practice of this method in Lithuania, particularly in foreign language teaching (FLT). Thus, teachers’ professional preparation for the effective implementation of PhenoBL remains one of the most relevant research problems. For this reason, this study aims to analyse the experiences of Lithuanian foreign language teachers in incorporating PhenoBL into FLT. Fifteen individual semi-structured interviews were conducted, and the obtained data were analysed by applying qualitative inductive content analysis. An inductive content analysis of the interview reports revealed six themes and related categories: the perception of student-centred teaching, the development of subject integration competencies, teamwork development competencies, research-planning skills, the positioning of personal responsibilities and duties, and foreign language usage emancipation, i.e. setting free from personal fears (fear to make grammar, vocabulary mistakes, while speaking in public) to speak a foreign languages. The content of the revealed themes indicated that teachers highlighted the flexibility of PhenoBL from the perspective of its application to different language learning levels within one group. The majority of the respondents underlined the necessity for the development of an active didactic competence. Other respondents mentioned the importance of the correlation between personal creativity competence development and success in PhenoBL. It was also stressed that if a teacher wants to be successful while using PhenoB, they must to be prepared to work with integration-based and communication-emancipatory methods, must be student-centred, must have competencies in teaching several subjects, must be good at teamwork, and must be good at managing learning time.